2018
DOI: 10.1021/acs.jpcc.8b02983
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Deformation Mechanisms for 1,3,5-Triamino-2,4,6-Trinitrobenzene Single Crystal through Molecular Dynamics Simulations

Abstract: The plastic behavior of the insensitive energetic molecular crystal 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) is investigated through molecular dynamics simulations.A recent method, built to follow any prescribed deformation path, is used to apply directional shear and compressive deformations to a TATB single crystal, leading to the tridimensional characterization of its nucleation von Mises stresses σ v (θ, φ), where θ and φ are the two angles (latitude and longitude, respectively) that define the loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 33 publications
9
75
1
Order By: Relevance
“…These results are consistent with the results of recent MD simulations of controlled uniaxial strain and strain-rate deformation [60] and 1.0 km s À 1 shock-wave simulations [73] of TATB, both performed for the case of no pre-existing defects and using essentially the same force field as here.…”
Section: Shock Parallel To the Molecular Layerssupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with the results of recent MD simulations of controlled uniaxial strain and strain-rate deformation [60] and 1.0 km s À 1 shock-wave simulations [73] of TATB, both performed for the case of no pre-existing defects and using essentially the same force field as here.…”
Section: Shock Parallel To the Molecular Layerssupporting
confidence: 91%
“…Practically, this dictates that defects which nucleate and grow to more than approximately two crystallographic unit‐cells extent along the thin direction will either be blocked or fill the sample at an unrealistic density along the shock direction, due to geometric constraints imposed by the periodic boundary conditions. However, we think the salient features of the collapse studied here would be preserved for cylindrical collapse in fully 3D simulation domains: Prior to shock arrival at the upstream pore surface, the present simulations yield deformation mechanisms that are qualitatively similar to those reported for controlled‐strain, controlled strain‐rate, rigid‐molecule MD simulations of initially defect‐free TATB as well as all‐atom MD simulations of explicit shocks in oriented, initially defect‐free 3D (as opposed to quasi‐2D) samples .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…21 A monoclinic polymorph, also layered, has been reported recently at room temperature for pressures greater than 4 GPa. 22 The high degree of structural anisotropy leads to significant anisotropy in the mechanical, [23][24][25][26][27][28][29][30][31][32][33][34] thermal, [35][36][37][38][39][40][41][42][43][44][45][46][47] and spectroscopic 21 properties of the substance. See Figure 1 for a view of a TATB crystal and additional information pertinent to the shock simulation geometry and crystal orientations studied here (detailed below).…”
Section: Introductionmentioning
confidence: 99%
“…Atomic-based studies of the non-shock mechanical response of TATB have also been reported. 22,[24][25][26]28,29,[67][68][69] Because of the nature of the crystal packing, plasticity involving slip between basal planes in TATB (the crystal exhibits two inequivalent basal planes) is expected to occur with much lower barriers to dislocation glide (i.e., stacking-fault energies), 70 in a fashion somewhat analogous to that in graphite, 71 compared to slip that occurs within a given molecular layer or that involves dislocation glide across multiple basal planes (both of which involve disrupting the intermolecular hydrogen-bonding network that exists within the layers). Indeed, using MD, very low stacking fault energies, and thus easy dislocation glide, were predicted for slip between adjacent basal planes both at zero kelvin 24 and at finite temperature.…”
Section: Introductionmentioning
confidence: 99%